PREVALENCE OF AUTISM SPECTRUM DISORDERS (ASD) AND ATTENTION DEFICIT HYPERACTIVITY DISORDERS (ADHD) AMONG ADULT PSYCH - Sana Khan (Army Medical College Rawalpindi, 2019)
Objective: To determine undiagnosed burden of autism spectrum disorder and attention deficit hyperactivity disorder and associated socio-demographic factors among adult psychiatric patients.